IMPLEMENTATION OF DISCOVERY LEARNING MODEL TO IMPROVE LEARNING RESULT OF NATURAL SCIENCE AT FIFTH GRADE OF SD KATOLIK ST. PAULUS KEMBES - Walewangko, Stief Aristo (Metodik Didaktik : Jurnal Pendidikan Ke-SD-an, 2019)
This study was intended to describe the application of Discovery Learning Model on natural science subject and to improve teacher’s skill and learning result of student on fifth grade of Elementary School. This research was classroom action research conducted in two cycles. Each cycle consists of planning, action, observation and reflection. Subjects of this research were students at fifth grade of SD Katolik St. Paulus Kembes. The collecting data technique was using test and observation. Technique of analyzing data was using quantitive descriptive analysis and qualitative descriptive analysis. The results showed that: 1) teacher’s skill in first cycle gained score 25 or 71,42% with ‘good’ criteria, and in second cycle obtained score 29 or 82,85% also with ‘good’ criteria; 2) student’s learning result in first cycle was 62,2% and the second cycle was 81,6%. These results concluded that the application of Discovery Learning Model can improve the quality of natural science subject learning, such as: teacher’s skill and learning result of the fifth grade student in SD Katolik St. Paulus Kembes. It was suggested that Discovery Learning model can be used as teacher’s solution to improve the quality of natural science learning.